Cannabis legalization, tobacco prevention policies, and Cannabis use in E-cigarettes among youth. (1st January 2020) - Nicksic, Nicole E.; Do, Elizabeth K.; Barnes, Andrew J.
Highlights: The US regulatory landscape of tobacco and cannabis products continues to evolve. This study characterized youth who had ever used cannabis in e-cigarettes. Cannabis laws were associated with increased cannabis in e-cigarette ever use. Tobacco prevention laws should consider how cannabis laws influence tobacco use. Abstract: Background: E-cigarettes are the most popular tobacco product among youth. As more states adopt cannabis legalization policies, youth cannabis use in e-cigarettes is a mounting concern. Methods: Data were from the 2016 and 2017 National Youth Tobacco Survey, a nationally-representative repeated cross-sectional survey administered to US middle and high school students. Ever use groups were categorized into e-cigarette ever users, cannabis in e-cigarette ever users, other tobacco ever users, and never users. Weighted multinomial logistic regression compared ever use groups, while controlling for state-level cannabis legalization and tobacco prevention polices, tobacco perceptions and exposures, and sociodemographic variables. Weighted prevalence of ever and current, or past 30 day, tobacco product use was determined by ever use groups. Results: Compared to e-cigarette ever users, cannabis in e-cigarette ever users increased (Adjusted Relative Risk Ratio (ARRR) = 1.65; p < 0.01) from 2016 to 2017. Medical-only and medical and recreational cannabis laws, and no e-cigarette minimum legal sales age (MLSA) and increased e-cigarette MLSA at 19 or 21 were positively associated with cannabis in e-cigarette ever users (ARRR = 1.34–1.85; p < 0.01, each). Ever and current use of all individual tobacco products was highest among cannabis in e-cigarette ever users compared to e-cigarette and other tobacco ever users. Conclusions: Cannabis use in e-cigarettes has increased among youth, and these trends will likely continue as e-cigarettes continue to gain popularity and cannabis legalization policies proliferate. Targeted tobacco and cannabis prevention strategies are needed for youth, especially in states that have implemented cannabis 'medical and recreational laws.